2010
DOI: 10.1104/pp.109.142349
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence of Endomembrane Trafficking and Actin Dynamics during Polarized Growth of Arabidopsis Pollen Tubes      

Abstract: During polarized growth of pollen tubes, endomembrane trafficking and actin polymerization are two critical processes that establish membrane/wall homeostasis and maintain growth polarity. Fine-tuned interactions between these two processes are therefore necessary but poorly understood. To better understand such cross talk in the model plant Arabidopsis (Arabidopsis thaliana), we first established optimized concentrations of drugs that interfere with either endomembrane trafficking or the actin cytoskeleton, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(97 citation statements)
references
References 46 publications
4
93
0
Order By: Relevance
“…RabA4b is a Rab GTPase that specifically decorates vesicles found in this inverted area of the apical region of pollen tubes (Lee et al, 2008;Zhang et al, 2010b) and Arabidopsis root hairs (Preuss et al, 2004). Consistent with previous findings (Lee et al, 2008;Zhang et al, 2010b), YFP-RabA4b accumulated at the apical region of wild-type pollen tubes, forming a concentrated inverted "V" shape (see Supplemental Figure 7A online). However, RabA4b-labeled vesicles at the subapex in vln2 vln5 pollen tubes were more uniformly distributed and dimmer (see Supplemental Figure 7A online).…”
Section: The Distribution Of Transport Vesicles Was Altered In Vln2 Vsupporting
confidence: 74%
“…RabA4b is a Rab GTPase that specifically decorates vesicles found in this inverted area of the apical region of pollen tubes (Lee et al, 2008;Zhang et al, 2010b) and Arabidopsis root hairs (Preuss et al, 2004). Consistent with previous findings (Lee et al, 2008;Zhang et al, 2010b), YFP-RabA4b accumulated at the apical region of wild-type pollen tubes, forming a concentrated inverted "V" shape (see Supplemental Figure 7A online). However, RabA4b-labeled vesicles at the subapex in vln2 vln5 pollen tubes were more uniformly distributed and dimmer (see Supplemental Figure 7A online).…”
Section: The Distribution Of Transport Vesicles Was Altered In Vln2 Vsupporting
confidence: 74%
“…37 More importantly, genes known to play a key role in cell-wall loosening and expansion, such as expansins, 1-3 glucanase and XET, were significantly expressed in the embryos as early as 5 or 15 h of imbibition, namely before germination completion and radicle extension. 37 It has been proposed that the endocytic delivery of cell wall pectins represents a ready-to-use reservoir of building blocks for rapid cell wall formation during cytokinesis 38 or cell expansion 39 and emerges to be critical for the polarity of pollen tubes. 40 So, the internalized RG-II observed here could operate as an intracellular pectin reservoir for the rapid cell expansion that proceeds upon imbibition.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate whether endocytosis is involved in the formation of SmaCCs/MASCs, we tested whether isoxaben-induced SmaCC/MASC formation is affected by perturbation of endocytosis by pharmacological and genetic means. Wortmannin (Wm) has been previously shown to inhibit the uptake of endocytic markers (Emans et al, 2002;Zhang et al, 2010). We examined FM4-64 internalization upon exposure to Wm in epidermal cells of etiolated hypocotyls.…”
Section: Endocytosis Is Involved In the Formation Of Stress-induced Smentioning
confidence: 99%
“…After 4.5 h of exposure to 33 mM Wm, epidermal cells of etiolated seedlings displayed fewer intracellular FM4-64 puncta. Quantification of the internalization of FM4-64 revealed that Wm exhibited an approximate 60% reduction in FM4-64 internalization compared with mock treatment (Supplemental Figure 9B) (Zhang et al, 2010). We also tested whether microtubule organization or dynamics were affected upon exposure to Wm.…”
Section: Endocytosis Is Involved In the Formation Of Stress-induced Smentioning
confidence: 99%